Arduino-based STEM student worksheet to improve scientific literacy in air pollution learning - Putri Irma Wahyuni; Rinie Pratiwi Puspitawati; Pramita Yakub; Arini Zahrotun Nasicha (Journal of Educational and Learning Studies, 2026)
Scientific literacy is a crucial competency for Biology Education students to understand scientific concepts and address environmental issues. However, Indonesian students' scientific literacy remains relatively low, indicating the need for innovative learning resources. This study aimed to develop and examine the validity, practicality, and effectiveness of an Arduino Uno-assisted STEM-based student worksheet on air pollution to improve scientific literacy. Using the Four-D (4D) model (define, design, develop, and disseminate), the worksheet was validated by two expert validators and tested on 36 Biology Education students. Data were collected through validation sheets, student response questionnaires, learning implementation observations, and pretest-posttest tests, then analyzed using validity percentages, practicality scores, and N-gain. The worksheet achieved a validity score of 91% (highly valid), practicality scores of 97.30–100% (very practical), and an average N-gain of 0.80 (high). Within the scope of this one-group pretest-posttest trial, these results indicate that the developed worksheet is valid, practical, and shows a promising initial effect for enhancing Biology Education students' scientific literacy.